Exploring the Integration of Technology in a Holistic Special Educational Setting. Issue 4 (4th July 2022) - Harris, Joe; Crawford, Lindy
ABSTRACT: Authors share an initial exploration of the pedagogy practiced at The Camphill School, specifically in relation to the integration of technology into its program. An approved private school situated in rural Pennsylvania, which caters to students on the autism spectrum, and others with different or additional physical and developmental disabilities, Camphill School works out of an adapted Waldorf curriculum, and integrates Waldorf Education, traditional special education strategies, and strategies informed by the curative educational approach to working with children and adolescents with intellectual disabilities and developmental delays. As a "tech-light" school, for pedagogical and therapeutic reasons, Camphill School has a pressing need to examine the current numbers of screen-based devices in the residential houses, classrooms, and therapy sessions, and the sharp increase in their presence in the last decade. This paper highlights several areas of concern related to the children's physical, and emotional wellbeing, and the wellbeing of the community in which the school is located. While research indicates a benefit to speech development for children using these devices, there are several gaps, which need to be examined, particularly for the population of children that is served. The necessity to preserve the organization's pedagogical integrity and identity as a school that provides a nurturing, natural environment for the children, while keeping abreast of trends in their professional field, leads to a series of recommendations in orienting toward the future.